The Negative Phase of the Blast Load. Issue 1 (March 2014) - Rigby, Sam E.; Tyas, Andrew; Bennett, Terry; Clarke, Sam D.; Fay, Stephen D.
Following the positive phase of a blast comes a period where the pressure falls below atmospheric pressure known as the negative phase. Whilst the positive phase of the blast is well understood, validation of the negative phase is rare in the literature, and as such it is often incorrectly treated or neglected altogether. Herein, existing methods of approximating the negative phase are summarised and recommendations of which form to use are made based on experimental validation. Also, through numerical simulations, the impact of incorrectly modelling the negative phase has been shown and its implications discussed.